Attapulgite-fly ash composite adsorbent as well as preparation method and application thereof

By combining natural concave and concave rock stone with fly ash, and using technical means such as acidification, hydrothermal precipitation, and high-temperature roasting, the concave rock stone-fly ash composite fluorine removal adsorbent was prepared, which solved the problems of low fluorine ion adsorption capacity and poor selectivity in the prior art, and achieved efficient fluorine ion adsorption effect.

CN119500059APending Publication Date: 2025-02-25CHINA UNIV OF MINING & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411498949.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When treating high fluorine wastewater in chemical plants, the adsorbent materials have problems such as low adsorption capacity, poor selectivity and narrow adaptation range of fluorine ions in the prior art. The traditional methods have limitations of secondary pollution and immature technology.

Method used

By combining natural concave and concave rock stone with fly ash, and using technical means such as acidification, hydrothermal precipitation, and high-temperature roasting, a concave rock stone-fly ash composite fluorine removal adsorbent is prepared to improve its adsorption performance on fluorine ions.

Benefits of technology

It realizes efficient adsorption of fluorine ions, with significantly better adsorption effect than natural concave and convex rock stones and fly ash, and has strong regenerative properties, and is suitable for fluorine-containing wastewater treatment in chemical plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500059A_ABST
    Figure CN119500059A_ABST
Patent Text Reader

Abstract

The invention discloses an attapulgite-fly ash composite adsorbent as well as a preparation method and application thereof, and the preparation method comprises the following steps: crushing, grinding and screening natural attapulgite, mixing with dilute sulphuric acid, carrying out constant-temperature oscillation treatment, washing to remove residual dilute sulphuric acid after reaction, filtering and drying to obtain acidified attapulgite; the preparation method comprises the following steps: adding acidified attapulgite into deionized water, heating and stirring, adding lanthanum chloride heptahydrate and polyaluminum chloride powder, and dropwise adding ammonia water at the same time to realize loading of lanthanum and aluminum on the surface of the acidified attapulgite; after heating and stirring, filtering and drying to obtain modified attapulgite; and mixing the modified attapulgite with fly ash, then carrying out mechanical grinding treatment, putting the ground sample into a tubular furnace, and carrying out anaerobic roasting to obtain the attapulgite-fly ash defluorination adsorbent. The attapulgite-fly ash defluorination adsorbent prepared by the invention has relatively strong selectivity and specific adsorption effect on fluorine ions in wastewater discharged by a chemical plant, and has renewability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, relates to the treatment of high-fluorine wastewater in chemical plants, and specifically relates to a preparation method and application of an attapulgite-fly ash defluorination adsorbent. Background Art

[0002] In recent years, water pollution has become increasingly serious. Many chemical plants discharge a large amount of fluoride-containing wastewater every year. Excessive fluoride ions will seriously threaten the safety of the water environment and human health. Therefore, how to treat this part of wastewater is an important issue that needs to be solved urgently. At present, the main treatment technologies for fluoride ions in water are membrane treatment, chemical precipitation, microbial method and adsorption method. The traditional membrane treatment method has problems such as easy damage and contamination of the filter membrane; the chemical precipitation method will produce fluoride precipitation and cause secondary pollution; the microbial method is not mature enough and has certain limitations. The adsorption method is simple to operate, widely used, and has good fluoride removal effect. It has obvious advantages over other technologies. Therefore, the research on high-performance adsorption materials is a current hot issue.

[0003] Attapulgite is a hydrous magnesium-aluminum silicate clay mineral. Attapulgite has a rich nanopore structure and a large specific surface area, and is a potential resource for high-quality adsorbents. However, natural attapulgite has a low grade, usually contains impurities such as quartz, dolomite, and mica, and lacks active sites that specifically adsorb fluoride ions. Therefore, natural attapulgite has a low fluoride adsorption capacity for water bodies and poor adaptability. It needs to be purified and modified to improve its adsorption performance. Lanthanum metal, as a rare earth element with abundant reserves, has strong selectivity and affinity for fluoride ions. It can complete coordination, complexation and ion exchange with fluoride ions in chemical wastewater to achieve fluoride removal from water bodies. In addition, aluminum oxide (hydroxide) is also widely used in the treatment of fluoride-containing wastewater.

[0004] Fly ash is the fine ash captured in the flue gas after the combustion of coal in thermal power plants. It is a typical coal-based solid waste. Its main components are SiO 2 、Al 2 O 3 ,FeO,Fe 2 O 3 , CaO, TiO 2 Fly ash has many pores and high mechanical strength, and has the potential to become a high-quality adsorbent, but its composition is relatively simple and has fewer active sites, so it has disadvantages such as low fluoride ion adsorption capacity, poor selectivity, and narrow adaptability. Composite adsorbents are a type of adsorbent that is currently being studied more widely. Two or more single adsorbents can be combined to obtain better adsorption performance. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a attapulgite-fly ash composite defluorination adsorbent, so as to realize high-value utilization by combining natural mineral materials with coal-based waste fly ash.

[0006] In order to achieve the above purpose, the following technical solutions are adopted: A method for preparing a attapulgite-fly ash composite adsorbent comprises the following steps: (1) crushing natural attapulgite, grinding the crushed attapulgite, sieving the ground attapulgite, mixing dilute sulfuric acid with the sieved attapulgite, and placing the mixture in a constant temperature oscillation box for constant temperature oscillation, washing to remove residual dilute sulfuric acid after the reaction, filtering, and drying to obtain acidified attapulgite; (2) adding the acidified attapulgite obtained in step (1) into deionized water, heating and stirring to fully disperse it, adding lanthanum chloride heptahydrate and polyaluminium chloride powder, and simultaneously dropping ammonia water to load lanthanum and aluminium on the surface of the acidified attapulgite; after heating and stirring, filtering and drying to obtain modified attapulgite; (3) The modified attapulgite obtained in step (2) is mixed with fly ash collected from a power plant, and then mechanically ground. The ground sample is placed in a tubular furnace for oxygen-free calcination to obtain a attapulgite-fly ash composite material, i.e., a attapulgite-fly ash defluorination adsorbent.

[0007] In the step (1), the screening particle size is below 200 mesh.

[0008] In the step (1), the concentration of dilute sulfuric acid is 10-15%.

[0009] In the step (1), the frequency of the constant temperature oscillation treatment is 180 r / min, the treatment time is 24-72 h, and the constant temperature is 25° C.

[0010] In the step (2), the mass ratio of acidified attapulgite to lanthanum chloride heptahydrate is 1:1, the mass ratio of acidified attapulgite to polyaluminium chloride is 3:1; the mass volume ratio of acidified attapulgite to deionised water is 3:100 g / ml; and the volume ratio of the added ammonia water to the mixed solution is 1:2.5.

[0011] In the step (2), during heating and stirring, the speed of the magnetic stirrer is 800 r / min, the temperature is 80° C., and the heating and stirring time is 6 h.

[0012] In the step (3), the mass ratio of modified attapulgite to fly ash is 4:1-1:4.

[0013] In the step (3), the oxygen-free condition is a nitrogen environment; the roasting time is 1-3 hours, and the roasting temperature is 300-900°C.

[0014] Another object of the present invention is to provide a attapulgite-fly ash defluorination adsorbent prepared by the above method.

[0015] Another object of the present invention is to provide the use of the above-mentioned attapulgite-fly ash defluorination adsorbent in the treatment of fluoride-containing wastewater.

[0016] The composite adsorbent prepared by the invention has a large specific surface area, a developed pore structure, and the modified attapulgite and fly ash are evenly distributed, which provides a large number of active sites for the adsorption of fluoride ions and can be used for treating fluoride-containing wastewater in chemical plants.

[0017] Compared with the prior art, the present invention has the following advantages: 1. The present invention uses natural clay mineral attapulgite and solid waste fly ash from thermal power plants as raw materials, and prepares attapulgite-fly ash composite materials by combining acidification, hydrothermal precipitation, and high-temperature roasting, which are used to purify fluorine-containing wastewater generated by chemical plants. The material has specific adsorption for fluoride ions, good adsorption effect, strong regeneration, and waste treatment, waste utilization, and combines natural mineral materials with coal-based waste fly ash for high-value utilization, which has great economic benefits and environmental value.

[0018] 2. The acidification treatment is intended to remove quartz and other gangue minerals in natural attapulgite, improve the purity of attapulgite, increase its internal pore structure, increase its specific surface area, and enhance its physical adsorption of fluoride ions; the lanthanum and aluminum modification treatment is intended to increase its surface active sites by loading lanthanum and aluminum that have specific adsorption to fluoride ions on the surface of the acidified attapulgite, and realize the selective adsorption of fluoride ions through coordination, complexation and ion exchange; the high-temperature calcination is intended to remove adsorbed water, bound water, etc. in fly ash and attapulgite, increase its specific surface area, and sinter the two materials to prepare attapulgite-fly ash composite adsorption material to adsorb and remove fluoride ions in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of the original attapulgite used in Example 1 of the present invention; Figure 2 is a scanning electron microscope image of the modified attapulgite used in Example 1 of the present invention; Figure 3 is a scanning electron microscope image of the original fly ash used in Example 1 of the present invention; Figure 4 This is a scanning electron microscope image of the attapulgite-fly ash composite material used in Example 1 of the present invention. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments. Example 1

[0021] (1) Acidification treatment: The natural attapulgite is crushed and ground, and the ground sample is passed through a 200-mesh sieve. 100 ml of 15% dilute sulfuric acid is mixed with 10 g of the sieved attapulgite, and the mixture is placed in a constant temperature oscillation box for 72 h at a frequency of 180 r / min and a constant temperature of 25°C. The residual dilute sulfuric acid is then washed to remove the residual sulfuric acid, filtered, and dried to obtain acidified attapulgite.

[0022] (2) Modification of attapulgite loading: 3 g of the acidified attapulgite obtained in step (1) was added to 100 ml of deionized water, and heated and stirred with a constant temperature magnetic stirrer to fully disperse it, with a constant temperature of 80°C and a rotation speed of 800 r / min. Subsequently, 3 g of lanthanum chloride heptahydrate and 1 g of polyaluminum chloride powder were added, and 40 ml of ammonia water was slowly added dropwise. The heating and stirring were continued for 6 hours to achieve the loading of lanthanum and aluminum on the surface of the acidified attapulgite. After the completion, the supernatant was discarded, filtered, and dried to obtain modified attapulgite.

[0023] (3) High-temperature calcination treatment: The modified attapulgite obtained in step (2) is mixed with fly ash collected from a power plant in a mass ratio of 1:4 and then mechanically ground. The ground sample is placed in a tubular furnace and calcined in the absence of oxygen at 700°C for 1 h to obtain a attapulgite-fly ash composite material, i.e., a attapulgite-fly ash defluorination adsorbent.

[0024] (4) Treatment of simulated fluorine-containing wastewater: 0.5 g of the attapulgite-fly ash defluorination adsorbent obtained in step (3) was added to 100 ml of simulated fluorine-containing wastewater with a fluoride ion concentration of 0.5 g / L. Dynamic adsorption was carried out for 24 h under constant temperature oscillation conditions with an oscillation frequency of 180 r / min and a temperature of 25°C. The fluoride ion concentration in the solution after adsorption was measured using a fluoride ion meter. The fluoride ion adsorption capacity of the composite adsorbent was calculated to be 256.6 mg / g, compared with the adsorption capacity of the original attapulgite of 48.0 mg / g and the adsorption capacity of the original fly ash of 206.3 mg / g under the same conditions.

[0025] Figure 1 This is a scanning electron microscope image of the original attapulgite used in this example. It can be seen that natural attapulgite contains many impurities. In addition to lamellar attapulgite, there are also a large number of granular gangue minerals with fewer pores. The specific surface area measured by the specific surface area analyzer is 65.66 m 2 / g, the adsorption activity is low. Figure 2This is a scanning electron microscope image of the modified attapulgite used in this example. It can be seen that compared with natural attapulgite, the surface of the modified attapulgite is loose and porous, the specific surface area is significantly increased, the pore structure is more developed, and no obvious gangue mineral structure is observed. The specific surface area measured by the specific surface area analyzer is 111.68 m 2 / g, indicating that a large amount of minerals have been removed and the existing structure is more conducive to the specific adsorption of fluoride ions. Through X-ray photoelectron spectroscopy and EDS analysis, it was found that lanthanum and aluminum were successfully loaded on the surface of attapulgite and were distributed relatively evenly, providing a large number of active sites for the adsorption of fluoride ions. Figure 3 The scanning electron microscope image of the original fly ash used in this example shows that the original fly ash is in block and granular form, with rich surface pores. The specific surface area measured by the specific surface area analyzer is 7.65 m 2 / g. Figure 4 The scanning electron microscope image of the attapulgite-fly ash composite material used in this example shows that the attapulgite is evenly distributed on the surface of the fly ash, and no obvious pore structure can be observed. The attapulgite and fly ash are sintered, and this structure is more conducive to the diffusion and adsorption of fluoride ions inside the composite material. The specific surface area measured by the specific surface area analyzer is 3.16 m 2 / g. Example 2

[0026] (1) Acidification treatment: The natural attapulgite is crushed and ground, and the ground sample is passed through a 200-mesh sieve. 100 ml of 15% dilute sulfuric acid is mixed with 10 g of the sieved attapulgite, and the mixture is placed in a constant temperature oscillation box for 72 h at a frequency of 180 r / min and a constant temperature of 25°C. The residual dilute sulfuric acid is then washed to remove the residual sulfuric acid, filtered, and dried to obtain acidified attapulgite.

[0027] (2) Modification of attapulgite loading: 3 g of the acidified attapulgite obtained in step (1) was added to 100 ml of deionized water, and heated and stirred with a constant temperature magnetic stirrer to fully disperse it, with a constant temperature of 80°C and a rotation speed of 800 r / min. Subsequently, 3 g of lanthanum chloride heptahydrate and 1 g of polyaluminum chloride powder were added, and 40 ml of ammonia water was slowly added dropwise. The heating and stirring were continued for 6 hours to achieve the loading of lanthanum and aluminum on the surface of the acidified attapulgite. After the completion, the supernatant was discarded, filtered, and dried to obtain modified attapulgite.

[0028] (3) High-temperature calcination treatment: The modified attapulgite obtained in step (2) is mixed with fly ash collected from a power plant in a mass ratio of 1:4 and then mechanically ground. The ground sample is placed in a tubular furnace and calcined in the absence of oxygen at 700°C for 2 h to obtain a attapulgite-fly ash composite material, i.e., a attapulgite-fly ash defluorination adsorbent.

[0029] (4) Treatment of simulated fluorine-containing wastewater: 0.5 g of the attapulgite-fly ash defluorination adsorbent obtained in step (3) was added to 100 ml of simulated fluorine-containing wastewater with a fluoride ion concentration of 0.5 g / L. Dynamic adsorption was carried out for 24 h under constant temperature oscillation conditions with an oscillation frequency of 180 r / min and a temperature of 25°C. The fluoride ion concentration in the solution after adsorption was measured using a fluoride ion meter. The fluoride ion adsorption capacity of the composite adsorbent was calculated to be 251.8 mg / g, compared with the adsorption capacity of the original attapulgite of 48.0 mg / g and the adsorption capacity of the original fly ash of 206.3 mg / g under the same conditions. Example 3

[0030] (1) Acidification treatment: The natural attapulgite is crushed and ground, and the ground sample is passed through a 200-mesh sieve. 100 ml of 15% dilute sulfuric acid is mixed with 10 g of the sieved attapulgite, and the mixture is placed in a constant temperature oscillation box for 72 h at a frequency of 180 r / min and a constant temperature of 25°C. The residual dilute sulfuric acid is then washed to remove the residual sulfuric acid, filtered, and dried to obtain acidified attapulgite.

[0031] 9) Modification of attapulgite loading: 3 g of the acidified attapulgite obtained in step (2) was added to 100 ml of deionized water, and heated and stirred with a constant temperature magnetic stirrer to fully disperse it, with a constant temperature of 80°C and a rotation speed of 800 r / min. Subsequently, 3 g of lanthanum chloride heptahydrate and 1 g of polyaluminum chloride powder were added, and 40 ml of ammonia water was slowly added dropwise. The heating and stirring were continued for 6 h to load lanthanum and aluminum on the surface of the acidified attapulgite. After the completion, the supernatant was discarded, filtered, and dried to obtain modified attapulgite.

[0032] (3) High-temperature calcination treatment: The modified attapulgite obtained in step (2) is mixed with fly ash collected from a power plant in a mass ratio of 1:4 and then mechanically ground. The ground sample is placed in a tubular furnace and calcined in the absence of oxygen at 700°C for 3 h to obtain a attapulgite-fly ash composite material, i.e., a attapulgite-fly ash defluorination adsorbent.

[0033] (4) Treatment of simulated fluorine-containing wastewater: 0.5 g of the attapulgite-fly ash defluorination adsorbent obtained in step (3) was added to 100 ml of simulated fluorine-containing wastewater with a fluoride ion concentration of 0.5 g / L. Dynamic adsorption was carried out for 24 h under constant temperature oscillation conditions with an oscillation frequency of 180 r / min and a temperature of 25°C. The fluoride ion concentration in the solution after adsorption was measured using a fluoride ion meter. The fluoride ion adsorption capacity of the composite adsorbent was calculated to be 251.7 mg / g, compared with the adsorption capacity of the original attapulgite of 48.0 mg / g and the adsorption capacity of the original fly ash of 206.3 mg / g under the same conditions. Example 4

[0034] (1) Acidification treatment: The natural attapulgite is crushed and ground, and the ground sample is passed through a 200-mesh sieve. 100 ml of 15% dilute sulfuric acid is mixed with 10 g of the sieved attapulgite, and the mixture is placed in a constant temperature oscillation box for 72 h at a frequency of 180 r / min and a constant temperature of 25°C. The residual dilute sulfuric acid is then washed to remove the residual sulfuric acid, filtered, and dried to obtain acidified attapulgite.

[0035] (2) Modification of attapulgite loading: 3 g of the acidified attapulgite obtained in step (1) was added to 100 ml of deionized water, and heated and stirred with a constant temperature magnetic stirrer to fully disperse it, with a constant temperature of 80°C and a rotation speed of 800 r / min. Subsequently, 3 g of lanthanum chloride heptahydrate and 1 g of polyaluminum chloride powder were added, and 40 ml of ammonia water was slowly added dropwise. The heating and stirring were continued for 6 hours to achieve the loading of lanthanum and aluminum on the surface of the acidified attapulgite. After the completion, the supernatant was discarded, filtered, and dried to obtain modified attapulgite.

[0036] (3) High-temperature calcination treatment: The modified attapulgite obtained in step (2) is mixed with fly ash collected from a power plant in a mass ratio of 1:4 and then mechanically ground. The ground sample is placed in a muffle furnace and calcined at 700°C for 3 h to obtain a attapulgite-fly ash composite material, i.e., a attapulgite-fly ash defluorination adsorbent.

[0037] (4) Treatment of simulated fluorine-containing wastewater: 0.5 g of the attapulgite-fly ash defluorination adsorbent obtained in step (3) was added to 100 ml of simulated fluorine-containing wastewater with a fluoride ion concentration of 0.5 g / L. Dynamic adsorption was carried out for 24 h under constant temperature oscillation conditions with an oscillation frequency of 180 r / min and a temperature of 25°C. The fluoride ion concentration in the solution after adsorption was measured using a fluoride ion meter. The fluoride ion adsorption capacity of the composite adsorbent was calculated to be 233.9 mg / g, compared with the adsorption capacity of the original attapulgite of 48.0 mg / g and the adsorption capacity of the original fly ash of 206.3 mg / g under the same conditions. Example 5

[0038] (1) Acidification treatment: The natural attapulgite is crushed and ground, and the ground sample is passed through a 200-mesh sieve. 100 ml of 15% dilute sulfuric acid is mixed with 10 g of the sieved attapulgite, and the mixture is placed in a constant temperature oscillation box for 72 h at a frequency of 180 r / min and a constant temperature of 25°C. The residual dilute sulfuric acid is then washed to remove the residual sulfuric acid, filtered, and dried to obtain acidified attapulgite.

[0039] (2) Modification of attapulgite loading: 3 g of the acidified attapulgite obtained in step (1) was added to 100 ml of deionized water, and heated and stirred with a constant temperature magnetic stirrer to fully disperse it, with a constant temperature of 80°C and a rotation speed of 800 r / min. Subsequently, 3 g of lanthanum chloride heptahydrate and 1 g of polyaluminum chloride powder were added, and 40 ml of ammonia water was slowly added dropwise. The heating and stirring were continued for 6 hours to achieve the loading of lanthanum and aluminum on the surface of the acidified attapulgite. After the completion, the supernatant was discarded, filtered, and dried to obtain modified attapulgite.

[0040] (3) High-temperature calcination treatment: The modified attapulgite obtained in step (2) is mixed with fly ash collected from a power plant in a mass ratio of 1:4 and then mechanically ground. The ground sample is placed in a muffle furnace and calcined at 900°C for 3 h to obtain a attapulgite-fly ash composite material, i.e., a attapulgite-fly ash defluorination adsorbent.

[0041] (4) Treatment of simulated fluorine-containing wastewater: 0.5 g of the attapulgite-fly ash defluorination adsorbent obtained in step (3) was added to 100 ml of simulated fluorine-containing wastewater with a fluoride ion concentration of 0.5 g / L. Dynamic adsorption was carried out for 24 h under constant temperature oscillation conditions with an oscillation frequency of 180 r / min and a temperature of 25°C. The fluoride ion concentration in the solution after adsorption was measured using a fluoride ion meter. The fluoride ion adsorption capacity of the composite adsorbent was calculated to be 225.7 mg / g, compared with the adsorption capacity of the original attapulgite of 48.0 mg / g and the adsorption capacity of the original fly ash of 206.3 mg / g under the same conditions.

[0042] By comparing the above embodiments, it can be seen that compared with natural attapulgite and original fly ash, the attapulgite-fly ash composite material has stronger adsorption selectivity for fluoride ions, and the composite material calcined in a tubular furnace without oxygen has better adsorption performance than that in a muffle furnace.

[0043] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a attapulgite-fly ash composite adsorbent, characterized in that: The following steps are involved: (1) crushing natural attapulgite, grinding the crushed attapulgite, sieving the ground attapulgite, mixing dilute sulfuric acid with the sieved attapulgite, and placing the mixture in a constant temperature oscillation box for constant temperature oscillation, washing to remove residual dilute sulfuric acid after the reaction, filtering, and drying to obtain acidified attapulgite; (2) adding the acidified attapulgite obtained in step (1) into deionized water, heating and stirring to fully disperse it, adding lanthanum chloride heptahydrate and polyaluminium chloride powder, and simultaneously dropping ammonia water to load lanthanum and aluminium on the surface of the acidified attapulgite; after heating and stirring, filtering and drying to obtain modified attapulgite; (3) The modified attapulgite obtained in step (2) is mixed with fly ash collected from a power plant, and then mechanically ground. The ground sample is placed in a tubular furnace for oxygen-free calcination to obtain a attapulgite-fly ash composite material, i.e., a attapulgite-fly ash defluorination adsorbent.

2. The method for preparing a attapulgite-fly ash composite adsorbent according to claim 1, characterized in that: In the step (1), the screening particle size is below 200 mesh.

3. The method for preparing a attapulgite-fly ash composite adsorbent according to claim 1, characterized in that: In the step (1), the mass concentration of dilute sulfuric acid is 10-15%.

4. The method for preparing a attapulgite-fly ash composite adsorbent according to claim 1, characterized in that: In the step (1), the frequency of the constant temperature oscillation treatment is 180 r / min, the treatment time is 24-72 h, and the constant temperature is 25° C.

5. The method for preparing a attapulgite-fly ash composite adsorbent according to claim 1, characterized in that: In the step (2), the mass ratio of acidified attapulgite to lanthanum chloride heptahydrate is 1:1, the mass ratio of acidified attapulgite to polyaluminium chloride is 3:1; the mass volume ratio of acidified attapulgite to deionised water is 3:100 g / ml; and the volume ratio of the added ammonia water to the mixed solution is 1:2.

5.

6. The method for preparing a attapulgite-fly ash composite adsorbent according to claim 1, characterized in that: In the step (2), during heating and stirring, the speed of the magnetic stirrer is 800 r / min, the temperature is 80° C., and the heating and stirring time is 6 h.

7. The method for preparing a attapulgite-fly ash composite adsorbent according to claim 1, characterized in that: In the step (3), the mass ratio of modified attapulgite to fly ash is 4:1-1:

4.

8. The method for preparing a attapulgite-fly ash composite adsorbent according to claim 1, characterized in that: In the step (3), the oxygen-free condition is a nitrogen environment; the roasting time is 1-3 hours, and the roasting temperature is 300-900°C.

9. An attapulgite-fly ash defluorination adsorbent prepared by the method according to any one of claims 1 to 8.

10. Use of the attapulgite-fly ash defluorination adsorbent according to claim 9 in the treatment of fluoride-containing wastewater.

Citation Information

Cited By

  • Fluorine and phosphorus synergistic prevention and control material for farmland soil with high-fluorine geological background and preparation method of fluorine and phosphorus synergistic prevention and control material

    CN120775596A